Developing a stochastic model for partial discharge detection in voids of polymeric cable insulation - Questelles, Kenroy Alexander (2006)
The detection of Partial Discharge (PD) is a useful tool in the maintenance and operation of electrical high voltage power cables. It has attracted many research and development efforts within the past one and a half decade. However, questions regarding the analysis and interpretation of PD data are still unanswered. In this research, an attempt is made to develop a simulation programme that can be used for developing a better understanding of the nature of PD phenomena based on its stochastic nature. It is done in consideration to the statistical properties of measured PD data from previous research, as well as the use of trial and error to obtain some parameters. Simulation was done in an effort to reconstruct the electrical field model of voids in polymeric cables using MATLAB M-files and statistical data from Phase Resolve Partial Discharge (PRPD) patterns. Such modeling can work for both electrical and acoustic data and may be used as a basis for comparison of future PD detection outcomes. The results indicates that the model worked well in the reconstruction of the field patterns of voids from given time and statistical data using the computer programme developed. Though the time was limited, the result seems to present new insight regarding the field patterns in the void. Phase and time data were combined in an effort to realize the objectives.